2014
DOI: 10.3346/jkms.2014.29.2.183
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bacteriostatic Effects of Rifampin onOrientia tsutsugamushi

Abstract: We performed an in vitro cell culture experiment to ascertain whether rifampin exhibits bactericidal effects against Orientia tsutsugamushi, the causative agent of scrub typhus. ECV304 cells were infected with the Boryong or AFSC-4 strain of O. tsutsugamushi and then, the cultures were maintained in media with increasing concentrations of rifampin, azithromycin, doxycycline, or chloramphenicol for 4 days. On day 5, the media were replaced with fresh antibiotic-free medium and the cultures were maintained until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Another study has noted the migratory capacity of MSC [ 50 ]. MSC enhance axon regeneration not only when delivered to the injured nerve or conduit bridging the nerve gap [ 26 , 39 , 51 ], but also when administered intravenously [ 27 , 30 , 52 ]. The MSC migration potential makes possible their detection at the site of sciatic nerve injury on day 7 post intravenous injection to mice and enhance functional recovery of the sciatic nerve [ 27 ].…”
Section: Cell Types Used In Cell Therapy For Nerve Regenerationmentioning
confidence: 99%
“…Another study has noted the migratory capacity of MSC [ 50 ]. MSC enhance axon regeneration not only when delivered to the injured nerve or conduit bridging the nerve gap [ 26 , 39 , 51 ], but also when administered intravenously [ 27 , 30 , 52 ]. The MSC migration potential makes possible their detection at the site of sciatic nerve injury on day 7 post intravenous injection to mice and enhance functional recovery of the sciatic nerve [ 27 ].…”
Section: Cell Types Used In Cell Therapy For Nerve Regenerationmentioning
confidence: 99%
“…CorA was unable to prevent the establishment of latent O. tsutsugamushi infections. Persistence of O. tsutsugamushi after antimicrobial treatment has been observed in all commonly used classes of antimicrobials (28,41). When we induced bacterial reactivation by cyclophosphamide 647 days p.i., viable O. tsutsugamushi organisms from lung homogenates could still be inhibited by CorA concentrations down to the previously determined MIC of 0.0078 g/ml, suggesting that persistence was unrelated to the selection of resistant mutants.…”
Section: Discussionmentioning
confidence: 85%
“…By demonstrating the effectiveness of CorA in vitro and in vivo, our study introduces inhibition of the bacterial RNAP switch region with ␣-pyrone antibiotics as a new and highly potent therapeutic target for treatment of O. tsutsugamushi infections. The rifamycins that also target RNAP, including rifampin, have long been known to be active against O. tsutsugamushi and are favored in areas where poor doxycycline responsiveness has been reported (10,34,41,42). Given the crucial role of rifampin as a first-line bacteriostatic drug in tuberculosis treatment, it was recognized early that rifampin is not an ideal standard regimen for treatment of scrub typhus.…”
Section: Discussionmentioning
confidence: 99%
“…These antibiotics have demonstrated high therapeutic efficacies and no cases with relapse; rifampin, in particular, has a bactericidal effect on certain bacteria [ 7 , 8 ]. A previous in vitro experiment, however, indicated that these antibiotics are also bacteriostatic against O. tsutsugamushi [ 9 ]. A combination antibiotic therapy may also be considered for this purpose, although an in vitro experiment revealed that this modality is not more effective than a single antibiotic [ 10 ].…”
Section: Introductionmentioning
confidence: 99%